Advances in Molecular Biology Methods in Hepatology Research (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Recent advances in molecular biology methods have profound implications for deciphering the complexities of hepatology research, specifically in understanding liver function, disease development, and novel therapies. The integration of genomic and proteomic technologies such as Next-Generation Sequencing (NGS), single-cell sequencing, CRISPR-Cas9, sensitive mass spectrometry, high-throughput proteomics, and epigenetic studies allow for a more comprehensive analysis of the liver's genomic landscape. These technologies enable scientists to understand the molecular pathways involved in liver injury, fibrosis, and regeneration. In addition to advances in genomic techniques, the development of advanced hepatic in vivo models and liver tissue engineering, utilizing technologies such as CRISPR-Cas9, places a clear emphasis on creating humanized organoid models. These molecular innovations, like hepatic organoids, are scalable for high-throughput screening and can replicate complex cellular interactions, providing further insights into the mechanisms underlying liver diseases such as metabolic dysfunction-associated steatotic liver disease (MASLD), hepatitis, and liver fibrosis. By creating patient-derived organoids, researchers can personalize disease models and uncover individualized disease mechanisms and precision therapeutics. Overall, these advancements in molecular biology have propelled hepatology research to the next level, offering additional opportunities for efficient diagnosis, treatment, and prevention strategies for hepatic diseases.